How Pentahelix Can Foster Institutional Capacity and Commitment (Study Case Coffee Business Development) - Dina Suryawati; Anwar Anwar; Agus Suharsono; Hermanto Rohman; Alfareza Firdaus (Program Pascasarjana Universitas Negeri Makassar, 2024)
Sekolah Kopi Raisa, a hybrid organization that empowers and educates communities, has an institutional model that other similar organizations might use. Penta helix players affect organization creation and performance. With a penta-helix approach, this study builds a model of Sekolah Kopi Raisa's commitment and institutional capability in coffee company growth. This study employs descriptive qualitative methods. Penta-helix players must support research findings to increase organizational commitment and capability. Both components boost corporate productivity and impact society. Penta helix actors promote organizational commitment and capacity development models, including change goals, influence, normative commitment, emotional, and shared vision. Human resources, networks, and structural development are other entities.